2019
DOI: 10.3390/medicina55110736
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and L-Lysine Aescinate for Acute Radiculopathy Due to a Herniated Lumbar Disk

Abstract: Background and objectives. The efficacy of commonly prescribed analgesic and adjuvant drugs for the management of patients with radiculopathy has not been well established. Oral steroids are commonly used to treat sciatica or radiculopathy due to a herniated disk but the effect remains controversial. L-lysine aescinate showed superiority over placebo or baseline therapy with NSAIDs alone in treating sciatica, but have not been evaluated in an appropriately powered clinical trial. Materials and Methods. Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…56 The peripheral nerves may not have been properly blocked depending on the form of anesthesia that was used in the included studies. Lysine has shown to have an analgesic effect in patients with herniated lumbar disk 57 and thus, hypothetically, TXA may reduce pain originating from the periosteum and reduce neurogenic inflammation. Studies investigating if TXA had a dose-response relationship with inflammation overall showed that a higher dose of TXA results in lower levels of inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The peripheral nerves may not have been properly blocked depending on the form of anesthesia that was used in the included studies. Lysine has shown to have an analgesic effect in patients with herniated lumbar disk 57 and thus, hypothetically, TXA may reduce pain originating from the periosteum and reduce neurogenic inflammation. Studies investigating if TXA had a dose-response relationship with inflammation overall showed that a higher dose of TXA results in lower levels of inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…56 The peripheral nerves may not have been properly blocked depending on the form of anesthesia that was used in the included studies. Lysine has shown to have an analgesic effect in patients with herniated lumbar disk 57 and thus, hypothetically, TXA may reduce pain originating from the periosteum and reduce neurogenic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids like dexamethasone have been routinely used to treat LDH. Oros et al 34 reported that intravenous injection of dexamethasone produced a long‐term analgesic effect in patients with acute radiculopathy and sciatica. Tagowski et al 12 found that dexamethasone was more effective in alleviating LDH‐induced radicular pain compared to that triggered by fixed stenotic spinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The deviations from intended interventions and missing outcome data domains were generally judged as low risk of bias. There were three studies [23][24][25] with high risk and one study 26 with some concerns due to inappropriate measurement of exposure. Nearly all studies (90%) were judged with high risk or some concerns of selective reporting.…”
Section: Risk Of Biasmentioning
confidence: 99%